Relationship of the structure of coordinational preparation and stability of competitive activity of female rhythmic gymnastics athletes - Dveyrina, O. A.; Viner, I. A.; Terekhina, R. N. (Theory and Practice of Physical Culture, 2024)
Objective of the study is to justify the introduction of new formats of cultural and sports events that ensure the growth of sports skills of gymnasts and allow, by taking into account the mechanism of interconnection of the structure of coordination readiness, to increase the stability of the competitive activity of female athletes in rhythmic gymnastics.